Restoring diversity of thermophilous oak forests: connectivity and proximity to existing habitats matter - Lanta, Vojtěch; Mudrák, Ondřej; Liancourt, Pierre; Dvorský, Miroslav; Bartoš, Michael; Chlumská, Zuzana; Šebek, Pavel; Čížek, Lukáš; Doležal, Jiří (Biodiversity and conservation, 2020)
The habitat fragmentation and isolation threaten populations of rare species. Organisms become endangered because of the primary habitat loss, but also due to limited dispersal capacity. Whether threatened species are limited more by their dispersal capacity or by lack of suitable habitats is an unresolved question critical to effective conservation. To address the question, we investigated patterns of colonisation by light demanding woodland plants in patches (clearings) of broadleaf forest where open canopy conditions were restored by partial cutting. Six pairs of identically sized (40 × 40 m) clearings were created in closed canopy thermophilous oak forest. Each pair included a clearing isolated in the closed forest and a clearing connected to an alluvial meadow and migration corridor along a river. Within each clearing, we followed colonization success by threatened and common species for 8 years. To assess the relative role of species pool, dispersal limitation and niche-based competition processes (viewed through the plant functional traits), we compared vegetation composition of the clearings to that of surrounding habitats (closed forest, open forest, meadow, forest edge). Clearings hosted more threatened species than closed forests, forest edges and meadows. Existing patches of open forest harboured the highest diversity of threatened species. Their proximity increased colonization success of threatened plants in clearings. Higher colonization rates by threatened plants were associated with shorter distances to source habitats and higher light, higher pH and lower moisture values in the clearings. Clearing type affected composition and ecological strategies of threatened species. Connected clearings were colonized by taller light-demanding species with higher seed mass, more suitable for establishment in a highly competitive environment, while the isolated clearings were colonized by shorter species with higher specific leaf area, better equipped for a more shaded environment. Species richness of threatened species increased in the first 3 years and decreased in last years, indicating that forest thinning creates only a short-term regeneration window with tree and shrub canopy closing back relatively fast. Active intervention should be therefore repeated in short intervals, preferably as shifting mosaics of differently aged stands. Our results bring novel information on the relative importance of habitat quality, isolation, and biotic filtering on communities of threatened species and their colonization success.